EVALUATION OF SOIL BEARING CAPACITY USING DYNAMIC CONE PENETROMETER (DCP) TEST AT VARIOUS DEPTH IN NORTH BARITO DISTRICT - Frans Putra Genesa; Nathanael Yanuar Kristianto; Lola Cassiophea; Muhtadin; Gagas Wira Syahputra (Jurusan Pendidikan Teknologi Dan Kejuruan, 2024)
This study evaluates soil bearing capacity in North Barito Regency using the Dynamic Cone Penetrometer (DCP) test. The objective is to analyze the relationship between penetration depth, number of blows (N-blows), and soil bearing capacity (Qall) across various locations, including Tumpung Laung, Muara Teweh, and Muara Laung villages. Testing was conducted up to a depth of 100 cm with data intervals every 10 cm. Results show a decrease in soil bearing capacity at specific depths, particularly in the shallow layer (0–20 cm), which is soft and less stable. Conversely, the middle layer (20–50 cm) and deeper layers (>50 cm) exhibit significantly higher bearing capacity, making them suitable for supporting heavy structures. Regression analysis revealed a strong relationship between depth, N-blows, and Qall, with coefficients of determination (R²) nearing or equal to 1 in most locations. Based on these findings, shallow foundations are recommended for light structures in middle layers, while deep foundations are necessary for heavy structures or locations with more variable soil characteristics, such as DCP 22. Soil improvement in shallow layers, such as re-compaction or geotextile usage, is strongly advised to enhance stability. This study highlights the importance of DCP testing in evaluating soil strength to support efficient and reliable foundation design. The findings are relevant for planning foundations, roadworks, and other infrastructure applications, particularly in areas with significant soil variability.